Fundamental Operation of Differential Transformation Method - T. Henson; G. Arunagiri (International Journal of Mathematics And its Applications, 2016)
This study deals about the application with fundamental operation of differential transformation method and is used to find the approximate solution for SIR model. SIR model are nonlinear system with fundamental operation of ordinary differential equation that has no analytic solution. DTM uses the fundamental operations of differential transformation function of the original nonlinear system. The result reveals that this method is accurate and efficient for solving systems of ordinary differential equations.